Suppressing dengue-2 infection by chemical inhibition of Aedes aegypti host factors. - Seokyoung Kang; Alicia R Shields; Natapong Jupatanakul; George Dimopoulos (Public Library of Science (PLoS), 2014)
Dengue virus host factors (DENV HFs) that are essential for the completion of the infection cycle in the mosquito vector and vertebrate host represent potent targets for transmission blocking. Here we investigated whether known mammalian DENV HF inhibitors could influence virus infection in the arthropod vector A. aegypti. We evaluated the potency of bafilomycin (BAF; inhibitor of vacuolar H+-ATPase (vATPase)), mycophenolic acid (MPA; inhibitor of inosine-5'-monophosphate dehydrogenase (IMPDH)), castanospermine (CAS; inhibitor of glucosidase), and deoxynojirimycin (DNJ; inhibitor of glucosidase) in blocking DENV infection of the mosquito midgut, using various treatment methods that included direct injection, ingestion by sugar feeding or blood feeding, and silencing of target genes by RNA interference (RNAi). Injection of BAF (5 µM) and MPA (25 µM) prior to feeding on virus-infected blood inhibited DENV titers in the midgut at 7 days post-infection by 56% and 60%, and in the salivary gland at 14 days post-infection by 90% and 83%, respectively, while treatment of mosquitoes with CAS or DNJ did not affect susceptibility to the virus. Ingestion of BAF and MPA through a sugar meal or together with an infectious blood meal also resulted in various degrees of virus inhibition. RNAi-mediated silencing of several vATPase subunit genes and the IMPDH gene resulted in a reduced DENV infection, thereby indicating that BAF- and MPA-mediated virus inhibition in adult mosquitoes most likely occurred through the inhibition of these DENV HFs. The route and timing of BAF and MPA administration was essential, and treatment after exposure to the virus diminished the antiviral effect of these compounds. Here we provide proof-of-principle that chemical inhibition or RNAi-mediated depletion of the DENV HFs vATPase and IMPDH can be used to suppress DENV infection of adult A. aegypti mosquitoes, which may translate to a reduction in DENV transmission.